Phenotypic complementation of genetic immunodeficiency by chronic herpesvirus infection - MacDuff, Donna A; Reese, Tiffany A; Kimmey, Jacqueline M; Weiss, Leslie A; Song, Christina; Zhang, Xin; Kambal, Amal; Duan, Erning; Carrero, Javier A; Boisson, Bertrand; Laplantine, Emmanuel; Israel, Alain; et al. (eLife, 2015)
Variation in the presentation of hereditary immunodeficiencies may be explained by genetic or environmental factors. Patients with mutations in HOIL1 (RBCK1) present with amylopectinosis-associated myopathy with or without hyper-inflammation and immunodeficiency. We report that barrier-raised HOIL-1-deficient mice exhibit amylopectin-like deposits in the myocardium but show minimal signs of hyper-inflammation. However, they show immunodeficiency upon acute infection with Listeria monocytogenes, Toxoplasma gondii or Citrobacter rodentium. Increased susceptibility to Listeria was due to HOIL-1 function in hematopoietic cells and macrophages in production of protective cytokines. In contrast, HOIL-1-deficient mice showed enhanced control of chronic Mycobacterium tuberculosis or murine γ-herpesvirus 68 (MHV68), and these infections conferred a hyper-inflammatory phenotype. Surprisingly, chronic infection with MHV68 complemented the immunodeficiency of HOIL-1, IL-6, Caspase-1 and Caspase-1;Caspase-11-deficient mice following Listeria infection. Thus chronic herpesvirus infection generates signs of auto-inflammation and complements genetic immunodeficiency in mutant mice, highlighting the importance of accounting for the virome in genotype-phenotype studies.
Keywords: Listeria monocytogene; murine gamma-herpesvirus 68; NF-kappaB; linear ubiquitination; immunodeficiency